Simple induction Proof ------------------------- Claim: The sum of the first n odd numbers is equal to n^2 Base case (n=1): the sum of the 1 odd numbers is just 1 = 1^2 Inductive Hypothesis: Assume the claim is true for n. Inductive step: We wish to prove the claim for n+1: From the induction hypothesis, we know that the sum of the first n numbers is n^2. We also know the (n+1)th odd number is equal to 2n+1. So the sum of the first n+1 odd numbers is n^2 + 2n + 1 = (n+1)^2. Thus, proving the claim for n+1. Therefore, by induction, the claim is true for all n >= 1. ------------------------------------------------------------ A more mathematical way ------------------------------------------------------------ Claim: From i = 1 to n, sum(2i-1) = n^2 Base case (n=1): sum(1) = 1 = 1^2 Inductive step: Assume the claim is true for n. We wish to prove the claim for n+1: From i=1 to n+1, sum(2i-1) = From i=1 to n, sum(2i-1) + 2(n+1)-1 = n^2 + 2(n+1) - 1 <--Induction hypothesis = n^2 + 2n + 1 = (n+1)^2 Therefore, by induction, the claim is true for all n >= 1.